A cluster objective PSO algorithm for optimal PMU placement in IEEE bus systems and in KPTCL grid. (2016) - Girish, V.; Ananthapadmanabha, T.
State estimation in power system requires the complete observability by phasor measurement units (PMU). The number of PMUs required for various utility applications are large. To reduce the number of PMUs, the placement problem in any network is considered as an optimisation problem. This paper presents a cluster objective particle swarm optimisation (CO-PSO) algorithm for optimal PMU placement. The proposed CO-PSO extracts the information of bus with maximum connectivity for PMU placement, checks whether any single node present in cluster area or not and periodically updates the cluster table with merging of neighbour bus to single node from PMU groups which reduces the PMU placement and computation time. The simulation results for IEEE bus and the KPTCL bus systems are presented and compared with the existing approaches. The proposed method offers lesser number of PMUs than the existing methods due to the new way of objective function formulation and cluster formation.